Several explanations on the theoretical formula of Helmholtz resonator. (December 2017) - Li, Lijun; Liu, Yiran; Zhang, Fan; Sun, Zhenyong
Highlights: The theoretic resonant frequency corresponds to the first order natural frequency. The cutoff frequency depends on acoustic cavity and independent of short tube. The resonant frequencies depend on the modes, and modes depend on geometry. Thickness difference of tube and cavity greater, correction length more accurate. The position of short tube influences the resonant frequency. Abstract: Helmholtz resonator is one of the most basic acoustic models in acoustic theoretical research and engineering applications. It is simple and effective to directly apply the theoretical formula for its resonant frequency calculation, but sometimes the calculation error is too large or even wrong. In this paper, the characteristics of Helmholtz resonators are studied based on the finite element numerical analysis. The influence of structural parameters and boundary conditions of the Helmholtz resonator on the resonant frequency is given, several related problems of the theoretical formula are supplemented and the relevant conclusions are obtained. The explanations employed in this paper could be used as a supplement to the theoretical formula for theoretical study and engineering applications of Helmholtz resonators.